Working Volume and Milling Time on the Product Size/Morphology, Product Yield, and Electricity Consumption in the Ball-Milling Process of Organic Material - Asep Bayu Dani Nandiyanto; Riezqa Andika; Muhammad Aziz; Lala Septem Riza (Indonesian Journal of Science and Technology, 2018)
Analysis of ball-milling process under various conditions (i.e. working volume, milling time, and material load) on the material properties (i.e. chemical composition, as well as particle size and morphology), product yield, and electricity consumption was investigated. Turmeric (curcuma longa) was used as a model of size-reduced organic material due to its thermally and chemically stability, and fragile. Thus, clear examination on the size-reduction phenomenon during the milling process can be done without considering any reaction as well as time-consuming process. Results showed that working volume is prospective to control the characteristics of product. Working volume manages the shear stress and the collision phenomena during the process. Specifically, the lower working volume led to the production of particles with blunt-edged morphology and sizes of several micrometers. Although working volume is potentially used for managing the final particle size, this parameter has a direct impact to the product yield and electricity consumption. Adjustment of the milling time is also important due to its relation to breaking material and electrical consumption.